SYSTEMATIC REVIEW OF THE IMPLEMENTATION OF THE TECHNOLOGY ACCEPTANCE MODEL (TAM) IN HOSPITAL INFORMATION MANAGEMENT SYSTEMS (HIMS) FOR IMPROVING HEALTH SERVICE QUALITY AND PATIENT SATISFACTION: A SYSTEMATIC LITERATURE STUDY - Wati, Wiwin Sri Niscahya (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the application of the Technology Acceptance Model (TAM) in adopting Hospital Information Management Systems (HIMS) and related healthcare technologies from 2020 to 2025. Method: Through a systematic literature review, 20 studies were analyzed to identify key factors influencing HIMS adoption, barriers, facilitators, and their impact on healthcare service quality and patient satisfaction. Results: Perceived usefulness (PU) and perceived ease of use (PEOU) consistently emerged as critical determinants of acceptance, underscoring the importance of user-friendly, functional designs. Privacy concerns, resistance to change, and inadequate training were identified as significant barriers, while organizational support, trust-building measures, and personalization facilitated adoption. The COVID-19 pandemic accelerated the adoption of telehealth and IoT solutions, highlighting the role of external factors in driving acceptance. However, sustaining long-term engagement requires robust security measures, adaptive technologies, and standardization of evaluation metrics. Novelty: This study offers actionable insights for healthcare administrators and policymakers to optimize HIMS adoption, improve operational efficiency, and enhance patient satisfaction.